A LiDAR application for the study of taxiway surface evenness and slope - M. Barbarella; M. R. De Blasiis; M. Fiani; M. Santoni (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2014)
Pavement roughness evaluation of airport runways/taxiways and scheduling of maintenance operations should be done according to well-defined procedures. Survey of geometric features of airport pavements is performed to verify the flow of water from the surface and to assure a level of roughness that allows the airplane to maneuver in the safest and most comfortable conditions. In particular the evaluation of longitudinal and transversal evenness of the runway and taxiway is carried out through topographic survey. The tachymetric survey has been carried out according to traditional topographic technique, which allows the evaluation of geometric position of isolated points with very high accuracy, but it is not very productive. Moreover it returns the pavement surface model through only few measured points. An alternative survey method, characterized by a good accuracy, high speed of acquisition and very high surveyed point density, is Terrestrial Laser Scanning (TLS), in static mode. In this paper we describe our experience aimed to validate the use of time-of-flight (TOF) TLS, based on a survey on a 200 m length segment of an international airport taxiway. From the acquired data we extracted the parameters of interest, especially the slope, and compared them with the values obtained from the traditional topographic survey. We also developed a proprietary software package to evaluate the slope and to analyze the statistical data. The software allows users to manage the flow of a semi-automatic calculation.